Facial nerve palsy, acute otitis media and Epstein-Barr virus infection - Diogo Cunha-Cabral; André Alves Carção; Pedro Marques Gomes; Gustavo Lopes; Delfim Duarte; José Ferreira Penêda (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Introduction: Facial nerve palsy is a rare complication of acute otitis media. Despite most cases are assumed to have a bacterial origin, in a significant proportion of them there are no clinical or laboratorial signs indicative of bacterial infection. A viral etiology was proposed in some of these cases.